Revolusi Hijau Berbasis Teknologi: Pelatihan Hidroponik sebagai Motor Pemberdayaan Ekonomi Desa Kembaran Wetan: Technology-Based Green Revolution Report: Hydroponic Training as a Driver of Economic Empowerment in Kembaran Wetan Village - Muhammad Amir Biky; Aditya Singgih Raharjo; Prasetyo Budi Wicaksana (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Indonesia faces major challenges in the agricultural sector, such as dependence on inefficient traditional methods and vulnerability to climate change. Kembaran Wetan Village, Purbalingga Regency, as an area with high population density and a large proportion of the community dependent on agriculture, has been affected by drought and has limited land and knowledge of modern agricultural technology. Therefore, this community service activity aims to empower the community through the introduction and training of a simple hydroponic system as a solution for agriculture in limited land areas, as well as a driver of the village economy. The methods used are participatory, including coordination with village officials, identification of needs, theoretical and practical training in wick-system hydroponic cultivation, establishment of demonstration plots, and mentoring and evaluation. The results of the activity showed a significant increase in participants' knowledge, as evidenced by an increase in the average evaluation score from 33.75 to 80.75. Participants, consisting of housewives and young people, were able to independently assemble hydroponic systems, sow pakcoy seeds, and care for plants. In addition, a demonstration plot was built to serve as a medium for continuous education. This activity successfully fostered motivation and changed the community's attitude towards the use of appropriate technology. In conclusion, hydroponic training has proven effective as a first step toward empowering the community to improve food security and expand economic opportunities. For sustainability, further assistance, institutional strengthening of the group, and integration of the program into village policies are needed to ensure optimal, independent economic impact.